2012
DOI: 10.1161/circulationaha.111.069245
|View full text |Cite|
|
Sign up to set email alerts
|

Important Differences in Mode of Death Between Men and Women With Heart Failure Who Would Qualify for a Primary Prevention Implantable Cardioverter-Defibrillator

Abstract: Background— Whether sex differences in implantable cardioverter-defibrillator (ICD) benefit exist remains unanswered. We evaluated sex differences in mode of death among a large cohort of ambulatory heart failure patients who meet criteria for a primary prevention ICD. Methods and Results— Patients from 5 trials or registries were included if they met American College of Cardiology/American Heart Association/Heart Rhythm Society guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 33 publications
2
35
0
1
Order By: Relevance
“…First, women in general have a lower susceptibility to ventricular arrhythmia compared with men18 and are less vulnerable to sudden death than men regardless of the presence of coronary artery disease,19 as our study confirmed. Among patients with heart failure potentially eligible for a primary prevention ICD, women are at lower risk of sudden death compared with men, and fewer of their deaths are sudden throughout a spectrum of all-cause mortality risk, irrespective of heart failure severity 20. Female patients implanted with an ICD/CRT-D experience fewer appropriate ICD therapies than men 8 18 21.…”
Section: Discussionmentioning
confidence: 99%
“…First, women in general have a lower susceptibility to ventricular arrhythmia compared with men18 and are less vulnerable to sudden death than men regardless of the presence of coronary artery disease,19 as our study confirmed. Among patients with heart failure potentially eligible for a primary prevention ICD, women are at lower risk of sudden death compared with men, and fewer of their deaths are sudden throughout a spectrum of all-cause mortality risk, irrespective of heart failure severity 20. Female patients implanted with an ICD/CRT-D experience fewer appropriate ICD therapies than men 8 18 21.…”
Section: Discussionmentioning
confidence: 99%
“…Men with coronary artery disease (CAD) in whom ICDs have been implanted have more ventricular tachycardia/ventricular fibrillation (VT/VF) events as well as more ICD shocks and electrical storms than women. 14 Lampert et al 15 reviewed the records of 340 men and 59 women with CAD who received an ICD and followed them for 30±22 months. They found that 52 % of the men experienced sustained VT or VF requiring ICD therapy (p<0.01) compared with 34 % of the women.…”
Section: Sex Differences In Primary Prevention Icdsmentioning
confidence: 99%
“…Improved targeting of ICD therapy may be better obtained by assessment of the underlying cause of systolic dysfunction or assessment of the degree of myocardial fibrosis . 45,46 Trends in Use of ICD Therapy Among Patients Hospitalized for HF: Have the Previously Observed Sex and Racial Disparities Changed Over Time?…”
Section: Discussionmentioning
confidence: 99%